PENINGKATAN KETERAMPILAN MENULIS KARANGAN PROSA MELALUI APLIKASI MODEL PEMBELAJARAN BERBASIS ILUSTRASI DI SEKOLAH DASAR - Muawanah, Siti (LP2M IAIN Palangka Raya, 2010)
Illustration based teaching learning in this study is the model of teaching learning using picture competency as the sketch illustration and photo which are provided to the students for prose composition assignment. The picture/sketch was developed from the simple model to the picture which stimulated the students to inspire in proposing the idea in writing. Based on the data analysis, the skill improvement of writing prose composition on the pre-test and post-test was different. From the different tests, it was concluded that there was significant different improvement between the skill improvement of writing prose composition and the development of illustration based teaching learning model on the pre-test and post-test. Based on the result of the study, the suggestions obtained are: 1) The teaching learning of illustration based writing is very potential if it is applied in the school in order to improve the studentsâ writing quality; 2) The positive attitude applied in the illustration based teaching learningÂ can be the basis of creating the effective learning situation.Â